Licochalcone A Upregulates Nrf2 Antioxidant Pathway and Thereby Alleviates Acetaminophen-Induced Hepatotoxicity - Lv, Hongming; Xiao, Qingfei; Zhou, Junfeng; Feng, Haihua; Liu, Guowen; Ci, Xinxin (Frontiers in Pharmacology, 2018)
Acetaminophen (APAP) overdose-induced fatal hepatotoxicity is majorly characterized by overwhelmingly increased oxidative stress while enhanced nuclear factor-erythroid 2-related factor 2 (Nrf2) is involved in prevention of hepatotoxicity. Although Licochalcone A (Lico A) upregulates Nrf2 signaling pathway against oxidative stress-triggered cell injury, whether it could protect from APAP-induced hepatotoxicity by directly inducing Nrf2 activation is still poorly elucidated. This study aims to explore the protective effect of Lico A against APAP-induced hepatotoxicity and its underlying molecular mechanisms. Our ﬁndings indicated that Lico A effectively decreased tert-butyl hydroperoxide (t-BHP)- and APAP-stimulated cell apoptosis, mitochondrial dysfunction and reactive oxygen species (ROS) generation and increased various anti-oxidative enzymes expression, which is largely dependent on upregulating Nrf2 nuclear translocation, reducing the Keap1 protein expression, and strengthening the antioxidant response element (ARE) promoter activity. Meanwhile, Lico A dramatically protected against APAP-induced acute liver failure (ALF) by lessening the lethality; alleviating histopathological liver changes; decreasing the alanine transaminase (ALT) and aspartate aminotransferase (AST) levels, malondialdehyde (MDA) formation, myeloperoxidase (MPO) level and superoxide dismutase (SOD) depletion, and increasing the GSH-to-GSSG ratio. Furthermore, Lico A not only significantly modulated apoptosis-related protein by increasing Bcl-2 expression, and decreasing Bax and caspase-3 cleavage expression, but also efficiently alleviated mitochondrial dysfunction by reducing c-jun N-terminal kinase (JNK) phosphorylation and translocation, inhibiting Bax mitochondrial translocation, apoptosis-inducing factor (AIF) and cytochrome c release. However, Lico A-inhibited APAP-induced the lethality, histopathological changes, hepatic apoptosis and mitochondrial dysfunction in WT mice were evidently abrogated in Nrf2 -/- mice. These investigations firstly implicated that Lico A has protective potential against APAP-induced hepatotoxicity which may be strongly associated with the Nrf2-mediated defense mechanisms.